2020
DOI: 10.1097/md.0000000000021959
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Ginkgo biloba for patients with early diabetic nephropathy

Abstract: Background: Diabetic nephropathy (DN) is not only an important microvascular complication of diabetes but also the main cause of end-stage renal disease. Ginkgo biloba has a variety of biological activities and has been widely used in China to treat kidney diseases such as DN. This article aimed to evaluate the efficacy and safety of G biloba in patients affected with DN in the early stage. Methods: This protocol fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…EGB761 contains flavonoids, terpene lactones, organic acids, and other chemical components, and it exerts several effects including antioxidant and free radical scavenging action, circulation improvement, platelet aggregation resistance, and nervous system protection [ 15 ]. Modern studies found that Ginkgo biloba injection significantly reduces 24-hour urinary microalbumin, total cholesterol, and triglyceride and improves renal function [ 16 , 17 ] in DKD patients, as well as relieves their clinical symptoms. However, its specific role and mechanism are needed to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…EGB761 contains flavonoids, terpene lactones, organic acids, and other chemical components, and it exerts several effects including antioxidant and free radical scavenging action, circulation improvement, platelet aggregation resistance, and nervous system protection [ 15 ]. Modern studies found that Ginkgo biloba injection significantly reduces 24-hour urinary microalbumin, total cholesterol, and triglyceride and improves renal function [ 16 , 17 ] in DKD patients, as well as relieves their clinical symptoms. However, its specific role and mechanism are needed to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Ginkgo biloba is an adaptive species and grows well in most parts of the world, including in the Mediterranean climate. The extract of Ginkgo biloba and/or its ginkgolide components, e.g., EGb761, BN52021, BN5739 and BN52063, possess many beneficial effects on the function of several injured and diseased cells and organs, including the nervous [ 116 , 117 , 118 , 119 , 120 ], renal [ 121 , 122 , 123 ] and cardiovascular [ 124 , 125 , 126 , 127 , 128 , 129 , 130 ] systems.…”
Section: Ginkgo Biloba “Ginkgoflavonoids” and Ho-1mentioning
confidence: 99%
“…There is still controversy about the clinical effects of GKB on blood metabolism in patients with T2DM. Some studies have suggested that GKB was beneficial in improving T2DM-related complications ( 2 , 7 , 10 ), but others found that the efficacy of GKB on diabetic macrovascular complications was not yet significant ( 11 ). Therefore, in this study, we analyzed the effects of ginkgo on blood metabolism in diabetic patients based on a large sample with comprehensive parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A serious concern for healthcare was diabetes mellitus (DM), which has several features including chronic hyperglycemia and aberrant protein, fat, and carbohydrate metabolism (2,(4)(5)(6). Diabetes is one of the five priority noncommunicable diseases (NCDs) in WHO's NCDs control strategy (7,8). Ongoing complex, expensive efforts are required to prevent and treat chronic problems in patients with diabetes, especially type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%